2007
DOI: 10.1111/j.1574-6941.2006.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Elsinochrome A production by the bindweed biocontrol fungus Stagonospora convolvuli LA39 does not pose a risk to the environment or the consumer of treated crops

Abstract: Biological control as an alternative to chemical pesticides is of increasing public interest. However, to ensure safe use of biocontrol methods, strategies to assess the possible risks need to be developed. The production of toxic metabolites is an aspect which has so far largely been neglected in the risk assessment and the registration process for biocontrol products. We have evaluated the risks of elsinochrome A (ELA) and leptosphaerodione production by the fungus Stagonospora convolvuli LA39, an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…These findings significantly add to earlier studies of our research group corroborating the potential of S. convolvuli LA39 as an efficient and risk‐free biocontrol agent (Ahonsi et al. 2006; Boss et al. 2007).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings significantly add to earlier studies of our research group corroborating the potential of S. convolvuli LA39 as an efficient and risk‐free biocontrol agent (Ahonsi et al. 2006; Boss et al. 2007).…”
Section: Discussionsupporting
confidence: 87%
“…The fate of Stagonospora convolvuli LA39 (Pfirter and Défago 1998) was investigated in two experiments conducted in areas with natural field and hedge bindweed infestation. A detailed description of cultivation and application of LA39 was provided in a previous study (Boss et al. 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Greenhouse experiments have revealed that Foxy 2 is effective and specific to S. hermonthica causing a reduction in Striga germination of up to 83% (Elzein and Kroschel 2004). To ensure the safe use of biocontrol methods, strategies to assess the associated risks need to be developed (Boss, Maurhofer, Schläpfer, and Defago 2007). For this, it is necessary first of all to understand the interactions between the biocontrol agent and the parasitic weed together with the host plant which is the non-target plant and the desired crop (Hearne 2009); before its implementation on large scale can be recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor complicating safety assessments of microbes for novel uses is the current lack of standardised test systems suitable for testing toxicity or pathogenicity of microorganisms with all their constituents and metabolites. Where specific metabolites of potential concern are known, toxicity studies can be performed with these compounds in pure form (Peltola et al , 2004; Boss et al , 2007). However, screening for toxic compounds without prior knowledge of the metabolites produced by a certain microbe requires that the tests be performed on the microbial cells themselves or cell homogenates.…”
Section: Introductionmentioning
confidence: 99%